On the fretting fatigue crack nucleation of complete, almost complete and incomplete contacts using an asymptotic method - Panico, Pierre; Chaise, Thibaut; Baietto, Marie-Christine; Guillemot, Nicolas; Poupon, Cédric (International journal of solids and structures, 2021)
In this work, the fretting crack nucleation of an aeronautical Ti-10V-2Fe-3Al titanium alloy is investigated. The main difficulty when designing complex industrial systems, especially helicopters rotor parts, lies in the prediction of the assembly interfaces behaviour. Those areas can be subjected to fretting loading characterized by a very confined multiaxial high stress gradient, leading to fatigue crack nucleation. This kind of failure reduces the parts potential lifetime and increases therefore the security margin that can be considered. The aim of this paper is to provide a criterion to prevent crack nucleation on industrial contacts configurations. To reach this objective, this study focuses on the geometrical conditions, loadings and material properties linked to crack initiation. Two dedicated fretting test campaigns are used to study crack initiation conditions with various contact shapes and loadings on the same material. The crack initiation conditions are compared with a contact mechanics representation based on asymptotic methods. This method allows the stress field evaluation at the hot spot location by using the problem’s eigenvalues. The combination of the asymptotic method with contact mechanics and the Goodman approach allows to represent the key parameters of the fretting fatigue crack initiation. They include the impacted material volume, the shear intensity and the bulk stress. A fretting fatigue crack initiation criterion is proposed. It is based on classical material properties and the bulk stress ratio Rσ0 only and is applicable to all sorts of contact shapes. The main interests of this prediction method are the absence of size effect parameters for industrial contacts and its efficiency, as it is only based on analytical formulations.